1997
DOI: 10.1021/np960533e
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Inhibitors from an Erythrina Species from Samoa

Abstract: Three flavonoid phospholipase A2 (PLA2) inhibitors were isolated from a MeOH extract of the bark of the Samoan medicinal plant Erythrina variegata. Two of these compounds, 4‘-hydroxy-3‘,5‘-diprenylisoflavonone (abyssinone V) (1) and 3,9-dihydroxy-2,10-diprenylpterocarp-6a-ene (erycrystagallin) (3), have been previously reported as antimicrobial agents from plants belonging to other Erythrina species. The isoflavonone 4‘-hydroxy-6,3‘,5‘-triprenylisoflavonone (2) is a new compound, and its structure was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…variegata has been used as a folk medicine in tropical and subtropical regions and is known to possess pharmacological activity, including antimicrobial and anti-inflammatory effects [20,21]. In a previous report, we isolated 16 isoflavonoids from the roots of this plant and showed that 3,9-dihydroxy-2,10-di(␥,␥-dimethylallyl)-6a, 11a-dehydropterocarpan (erycristagallin) and 9-hydroxy-3-methoxy-2-␥,␥-dimethylallylpterocarpan (orientanol B) exhibited substantial anti-MRSA activity with an MIC range of 3.13-6.25 mg/ml [22].…”
Section: Discussionmentioning
confidence: 99%
“…variegata has been used as a folk medicine in tropical and subtropical regions and is known to possess pharmacological activity, including antimicrobial and anti-inflammatory effects [20,21]. In a previous report, we isolated 16 isoflavonoids from the roots of this plant and showed that 3,9-dihydroxy-2,10-di(␥,␥-dimethylallyl)-6a, 11a-dehydropterocarpan (erycristagallin) and 9-hydroxy-3-methoxy-2-␥,␥-dimethylallylpterocarpan (orientanol B) exhibited substantial anti-MRSA activity with an MIC range of 3.13-6.25 mg/ml [22].…”
Section: Discussionmentioning
confidence: 99%
“…They include quercetin and some other flavones/flavonols such as scutellarein and nepetin. 4,[22][23][24] Several prenylated flavonoids including abyssinone V and papyriflavonol A were also reported as PLA 2 inhibitors. 25,26) In this respect, the present finding of new PLA 2 inhibitory flavonoid is meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol bark extract yielded chloroform-soluble and water-soluble bases, identifi ed as erysovine and stachydrine, respectively. From the bark were isolated isofl avones (erythrinins A,B, C, osajin; alpinumisofl avone; and oxyresveratrol and dihydrooxyresveratrol) (Deshpande et al 1977 ), alkaloids (erysotine, erythratidine, epi -erythratidine and 11-hydroxy-epi -erythratidine) (Chawla et al 1988 ), three fl avonoid phospholipase A 2 (PLA 2 ) inhibitors (4′-hydroxy-3′,5′-diprenylisofl avonone (abyssinone V) and 3,9-dihydroxy-2,10-diprenylpterocarp-6a-ene (erycrystagallin) and 4′-hydroxy-6,3′,5′-triprenylisofl avonone) (Hedge et al 1997), erythrinin B ( Kobayahsi et al 1997, alpinumisofl avone and two prenylated isofl avones (erythrivarones A and B characterized as dihydroalpinumisofl avone and 4′-hydroxy-[6″,6″-dimethyldihydropyrano(2″,3″:5,6)]-[6‴,6‴-dimethyldihy dropyrano(2‴,3‴:7,8)] isofl avone, respectively) (Huang and Yen 1996 ; and warangalone (Huang and Tseng 1998 ). Isofl avonoids, eryvarin A and eryvarin B, were isolated from wood (Tanaka et al 2000 ).…”
Section: Stem/bark/wood Phytochemicalsmentioning
confidence: 99%
“…Three isofl avones, abyssinone V (1), 4′-hydroxy-6,3′,5′-triprenylisofl avonone (2) and erycrystagallin (3), isolated from the bark, exhibited phospholipase A2 (PLA2) inhibition with IC 50 values of 6, 10 and 3 μM for 1 − 3, respectively (Hedge et al 1997 ). The methanol leaf extract was found to have antiinfl ammatory activity as observed by reduction of the paw oedema (Verma et al 2005 ).…”
Section: Antiinfl Ammatory Activitymentioning
confidence: 99%